Dr. Juha Hernesniemi, Visionary Neurosurgeon and Compassionate Healer - Kafle, Prakash (Nepal Journal of Neuroscience, 2023)
Dr. Juha Hernesniemi, a visionary in the field of neurosurgery, passed away on June 27, 2023, at the age of 75. Born on May 3, 1948, in Helsinki, Finland, Dr. Hernesniemi dedicated his life to advancing the understanding and treatment of complex neurovascular disorders.